Educational technology utilization in Jamaica's secondary school system: Present problems and future prospects - Jennings-Wray, Zellynne
This paper describes a study conducted to assess the use of educational television (ETV) and self-instructional materials (SIM) in Jamaica's secondary school system, and to determine factors affecting their implementation. Current trends in the adoption of educational technology in Jamaican secondary schools, and some implications for utilization in developing nations are discussed
DOI: 10.1111/j.1467-8535.1985.tb00706.x
Keywords: Educational television